Efficacy and safety of apatinib versus sorafenib/placebo in first-line treatment for intermediate and advanced primary liver cancer: A systematic review and meta-analysis - Dan Peng; Yongqing Cai; Geng Chen; Min Hou; Xiaofeng Luo; Zhuoma Dongzhi; Hongjun Xie; Yao Liu (Frontiers Media S.A., 2023)
Background: Apatinib is a novel tyrosine kinase inhibitor used in the treatment of advanced hepatocellular carcinoma (HCC). For decades, sorafenib has been a classic first-line treatment option for patients with HCC. This meta-analysis aimed to assess the efficacy and safety of apatinib versus sorafenib/placebo as first-line treatment for intermediate and advanced primary liver cancer (PLC).Methods: A literature search was performed via PubMed, Web of Science, CENTRAL, Embase, CNKI, VIP, and CBM. Data extraction from databases of other languages is not restricted. The Cochrane risk of bias tool, modified Jadad scale, Newcastle-Ottawa scale (NOS), and non-randomized studies of interventions (ROBINS-I) tool were employed to evaluate methodological qualities in original studies. Influence analysis was applied to assess the reliability of pooled results. Publication bias was evaluated using the funnel plot with Begg's test and Egger's test.Results: Seven studies were included in the systematic review and meta-analysis. Four randomized controlled trials (RCTs) and one clinical controlled trial (CCT) were used for comparing apatinib with placebo, and two retrospective clinical studies (RCSs) were used for comparing apatinib with sorafenib. Apatinib led to higher overall effects in objective response rate (ORR), disease control rate (DCR), and mean survival time (MST) over placebo (RR = 2.03, 95% CI = 1.46-2.81, p < 0.0001, I2 = 0%; RR = 1.17, 95% CI = 1.04-1.33, p = 0.009, I2 = 45.8%; SMD = 2.63; 95% CI = 1.47-3.78, p < 0.0001, I2 = 92.7%, respectively). Compared to sorafenib, apatinib showed no superiority in ORR and DCR but was inferior in the 6-month and 1-year survival rate (RR = 1.99, 95% CI = 0.85-4.65, p = 0.111, I2 = 68.3%; RR = 1.04, 95% CI = 0.73-1.47, p = 0.840, I2 = 0.0%; RR = 0.63, 95% CI = 0.42-0.97, p = 0.036, I2 = 0.0%; RR = 0.47, 95% CI = 0.29-0.79, p < 0.0001, I2 = 0.0%, respectively). Apatinib had similar adverse effects over placebo but possessed a greater incidence rate of proteinuria and hypertension over sorafenib.Conclusion: In the first-line setting, apatinib might be an alternative treatment approach for patients with intermediate and advanced PLC. Sorafenib alone showed a better survival rate within 1 year and a lower incidence rate in hypertension and proteinuria than apatinib monotherapy.